2014
DOI: 10.15252/msb.20145508
|View full text |Cite
|
Sign up to set email alerts
|

Rapid neurogenesis through transcriptional activation in human stem cells

Abstract: Advances in cellular reprogramming and stem cell differentiation now enable ex vivo studies of human neuronal differentiation. However, it remains challenging to elucidate the underlying regulatory programs because differentiation protocols are laborious and often result in low neuron yields. Here, we overexpressed two Neurogenin transcription factors in human-induced pluripotent stem cells and obtained neurons with bipolar morphology in 4 days, at greater than 90% purity. The high purity enabled mRNA and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
271
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(282 citation statements)
references
References 67 publications
10
271
1
Order By: Relevance
“…Previous work has shown that the ectopic expression of several cDNAs enables cellular reprogramming of terminally differentiated cells to a pluripotent state, and can similarly induce differentiation of stem cells into multiple cell types 25 . While such studies typically require multiple factors, it was recently shown that exogenous expression of single transcription factors, Neurogenin2 (NGN2) or Neurogenic differentiation factor 1 (NEUROD1), is sufficient to induce differentiation of human iPS cells into induced neurons (iNeurons) 26,27 . Our group had previously attempted to recapitulate this same differentiation paradigm using dCas9-VP64 based activators and observed minimal differentiation activity (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that the ectopic expression of several cDNAs enables cellular reprogramming of terminally differentiated cells to a pluripotent state, and can similarly induce differentiation of stem cells into multiple cell types 25 . While such studies typically require multiple factors, it was recently shown that exogenous expression of single transcription factors, Neurogenin2 (NGN2) or Neurogenic differentiation factor 1 (NEUROD1), is sufficient to induce differentiation of human iPS cells into induced neurons (iNeurons) 26,27 . Our group had previously attempted to recapitulate this same differentiation paradigm using dCas9-VP64 based activators and observed minimal differentiation activity (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…While the amount of iNeurons we observe upon dCas9-VPR mediated differentiation is less than 10% of the total cell population, it should be noted that the true proportion of differentiated cells is likely higher. Undifferentiated iPS cells continue to divide rapidly during our 4-day induction period while iNeurons are post-mitotic and thus remain under-represented at our analysis endpoint 26,27 . Another promising facet of our work is the ability to upregulate both endogenous coding and non-coding genes, paving the way for large-scale genomic screens free from constraints such as gene size or availability of previously constructed cDNA libraries 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Common protocols to differentiate neurons from human stem cells, such as dual SMAD inhibition or embryoid body differentiation, require months to create mature neurons (Zhang et al 2001;Chambers et al 2009). Recently, we and others have demonstrated that viral overexpression of Neurogenin 1 or Neurogenin 2 can rapidly drive stem cells into a homogeneous culture of mature cortical neurons (Zhang et al 2013;Busskamp et al 2014). These neurons display robust electrophysiological activity within just 2-3 weeks after the start of differentiation, making them ideally suited for synaptic assays, calcium imaging and neurophysiology.…”
Section: Bottom-up Approaches Using Exome Sequencing In Autismmentioning
confidence: 99%
“…In particular, the short maturation time, the unparalleled efficiency of induction, and the homogeneity of the neuronal population are key advances in the field. Pluripotent stem cell-derived iN cells are already suitable for robust, functional studies of cellular disease phenotypes as well as high-throughput screens for drug discovery [100].…”
Section: Direct Conversion Of Somatic Cells Versus Induction Of Plurimentioning
confidence: 99%